Evaluation Of The Implementation Of The Function Of Forming The Regional Regulations Council Of People's Representatives Rokan Hulu Region (2014-2019 Period) - Data Wardana; Syafhendry Syafhendry; Bayu Anggara (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
This research evaluates the function of the Regional People's Legislative Council of Rokan Hulu Regency for the 2014-2019 period in forming Regional Regulations. And there are indications that the Human Resources of the DPRD of Rokan Hulu Regency still need to be more decisive in the formation of regional regulations, so only a few local government regulation are passed at the initiative of the DPRD. In this study, the authors used qualitative methods. This research data collection technique by observation, interviews, and documentation. This research uses the theory of Policy Evaluation according to Ndraha, namely the Das Sollendas Sein Model, which compares what should be and should be. With indicators of Planning, Preparation, Discussion, Approval, Promulgation, and Dissemination. Based on the results of research on the Evaluation of the Implementation of the Function for Forming Regional Regulations of the Regional People's Representative Council of Rokan Hulu Regency (2014-2019 Period) that very few regional regulations were passed at the initiative of the DPRD, lack of understanding of community problems so that not many were responded to in the form of policies. So it is necessary to conduct training in making regional regulations to increase the understanding of council members in drafting regional regulations.